Keadilan Distributif dan Prosedural: Kunci Kepuasan Kerja dalam Arsitektur Remunerasi - Sanawi Sanawi; Ilham Hibatullah; Muhamad Lulu Kamaludin; Trisna Taufik Darmawansyah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the influence of distributive justice and procedural justice on job satisfaction of UIN Sultan Maulana Hasanuddin Banten employees in the Public Service Agency (BLU) remuneration scheme. Using a quantitative approach, a sample of 83 employees was purposively selected. The research instrument adopted the Colquitt scale and organizational behavior indicators with a Likert scale of 1–5. Data quality testing results showed all items were valid and reliable. The classical assumption test was met without multicollinearity or heteroscedasticity constraints. Multiple linear regression analysis produced the equation: Y = 19.966 + 0.215X1 + 0.202X2. Partially, both variables had a significant effect (p < 0.05). Simultaneously, the model proved significant (F = 8.135; p = 0.001) with an R2 value of 0.169, indicating a 16.9% contribution of the justice variable to job satisfaction. These findings confirm that job satisfaction is influenced by outcome justice (performance-based remuneration) and process justice (transparency and consistency of rules). Managerial recommendations include strengthening two-way communication, ensuring accurate performance data, and fostering participatory policy correction mechanisms. This research expands the literature on organizational justice at State Islamic Religious Universities (PTKIN) and provides direction for further research.